The phenotypic features used for distinguishing species within the Cladonia furcata complex are highly homoplasious. (9th September 2015) - Unknown
Abstract: The Cladonia furcata complex treated here comprises C. farinacea, C. furcata, C. multiformis, C. scabriuscula, C. stereoclada, and C. subrangiformis . The well-known taxonomic complexity of this group is caused by wide phenotypic variation and high morphological similarity among the species, for which reason we investigated the distribution in the phylogeny of the phenotypic characters traditionally used to distinguish the species in this complex. A phylogenetic analysis of the C. furcata complex is presented here, based on three loci (ITS rDNA, IGS rDNA and RPB2 ), representing specimens from a broad geographical range (Europe, North America and New Zealand). The phylogenetic reconstructions were performed using Maximum Likelihood and Bayesian analyses. In addition, 14 features traditionally used for species delimitation within this complex were mapped onto the Bayesian phylogeny. All the species currently accepted, with the exception of C. stereoclada, turned out to be polyphyletic. Most of the phenotypic characters studied are highly homoplasious with the exception of the podetium type. The solid podetia represent a diagnostic character of C. stereoclada.